University students’ digital world of work readiness in relation to their employability competency - Ingrid Potgieter; Melinde Coetzee; Nadia Ferreira (Journal of Learning Development in Higher Education, 2023)
This research empirically examined the extent to which university students’ perceptions about their readiness for the digital-era work world predict their sense of employability competency. Data were collected from 486 undergraduate students of a comprehensive South African distance learning higher education institution. Regression analysis and structural equation modelling revealed that students’ perceptions of their world of work readiness (i.e. job/occupation certitude and job/occupation fitness) significantly predict their sense of employability competency. The study highlights the importance of building confidence or certainty within students during their academic career about the knowledge, skills and occupations they want to pursue in the digital-era work sphere to positively influence their sense of employability competency. Should they feel positive about their work world readiness, they are more likely to exhibit the employability competency of business ingenuity and social digital agility which are deemed essential for the new normal work context.